The Influence of Digital Marketing and Service Quality on Consumer Purchasing Decisions Coffee Shop Lagi Lagi CHL Makassar City - Marhawati; Nurhidayah, AM. Fatwa; Supatminingsih, Tuti; Rahmatullah; Ampa, A. Tenri (Economics and Business Journal (ECBIS), 2023)
The purpose of this research is to determine the influence exerted by digital marketing and service quality on consumer purchasing decisions Coffee Shop Lagi lagi chl Makassar City. The research method used is quantitative with descriptive methodology. To collect research data for this study, questionnaires and documentation were both used. In this study, 50 people were used as samples, and the Likert scale method was used to calculate the number of samples. Partial test (t test), simultaneous test (f test), coefficient of determination (R2), and classical assumption test are the data analysis techniques used in this study. The research findings show that each factor used has a beneficial impact on consumer purchasing decisions Coffee Shop Lagi lagi chl as a result of Digital Marketing (X1) related to marketing knowledge. Quality of service (X2). Purchase decision (Y).